Potential assessment of Desmodesmus asymmetricus and Chlorella vulgaris for removal of nitrates and phosphates in wastewater - Oscanoa, Alberto Isidoro (2021)
In this work, we evaluated the proportion Chlorella vulgaris and Demodesmus asymmetricus microalgae, that removes the highest concentration of nitrogen and phosphorus in wastewater from a treatment plant. A mixture design was employed in this study, for 9 days, with 12:12 h photoperiod, in a greenhouse. The highest nitrogen removal efficiencies (mainly NO3--N and NO2--N) and phosphorus (PO43-) were observed in treatments with the highest proportion of D. asymmetricus, including T3 (25% C. vulgaris / 75 % D. asymmetricus), where 100.0% nitrogen and 77.1% phosphorus were removed. Likewise, T3 obtained the best result of dissolved oxygen (DO), achieving average of 10.90 ± 0.60 mg/L. Finally, according to the analysis of the mixture design, the optimal microalgae mixture was determinated that achieves the highest DO production, and the highest removal was the proportion of 6% of C. vulgaris and 94% of D. asymmetricus in 9 days cultivation time. In conclusion, microalgae have shown their capacity for bioremediation of domestic wastewater, which is an alternative to consider.